2021
DOI: 10.3389/fcvm.2021.676658
|View full text |Cite
|
Sign up to set email alerts
|

Are HFpEF and HFmrEF So Different? The Need to Understand Distinct Phenotypes

Abstract: Traditionally, patients with heart failure (HF) are divided according to ejection fraction (EF) threshold more or <50%. In 2016, the ESC guidelines introduced a new subgroup of HF patients including those subjects with EF ranging between 40 and 49% called heart failure with midrange EF (HFmrEF). This group is poorly represented in clinical trials, and it includes both patients with previous HFrEF having a good response to therapy and subjects with initial preserved EF appearance in which systolic functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…According to recently published studies, clinical profiles of patients allow for the discrimination between the three HF categories, especially the presence of comorbidities and quality of life based on the ESC guidelines (16)(17)(18)(19)(20)(21). Based on these clinical results, HFmEF patients were found to fall between HFpEF and HFrEF while more closely resembling HFpEF (22,23). Additionally, they were more likely to be younger than HFpEF and more prone to diabetes and hypertension than HFrEF (20,24).…”
Section: Introductionmentioning
confidence: 99%
“…According to recently published studies, clinical profiles of patients allow for the discrimination between the three HF categories, especially the presence of comorbidities and quality of life based on the ESC guidelines (16)(17)(18)(19)(20)(21). Based on these clinical results, HFmEF patients were found to fall between HFpEF and HFrEF while more closely resembling HFpEF (22,23). Additionally, they were more likely to be younger than HFpEF and more prone to diabetes and hypertension than HFrEF (20,24).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical-epidemiological studies have shown that patients with HFmrEF had different clinical characteristics and may be intermediate between the those with HFrEF or HFpEF. 22 In the meta-analysis of 12 observational studies with 109 257 patients, all-cause mortality and hospitalisation for HF were lower in patients with HFmrEF than in those with HFrEF and HFpEF. 23 However, the study population was heterogeneous, and only five studies provided outcomes of cardiovascular death or hospitalisation for HF.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, heart failure guidelines changed introducing a third category (heart failure with mid-range ejection fraction) with LVEF 40 to <50%( 27 , 49 ). This class shares features from HFrEF and HFpEF and is underrepresented in current studies ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our study shows that remote patient management may reduce all-cause mortality in the highly vulnerable population of patients with heart failure and CKD. In Germany telemedicine for patients with advanced heart failure has been implemented recently to further reduce mortality ( 50 53 , 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%